Gender as risk factor for 30 days post-discharge hospital utilisation: a secondary data analysis. Issue 2 (18th April 2012) - Woz, Shaula; Mitchell, Suzanne; Hesko, Caroline; Paasche-Orlow, Michael; Greenwald, Jeffrey; Chetty, V K; O'Donnell, Julie; Jack, Brian
Abstract : Objective: In the 30 days after hospital discharge, hospital utilisation is common and costly. This study evaluated the association between gender and hospital utilisation within 30 days of discharge. Design: Secondary data analysis using Poisson regression stratified by gender. Participants: 737 English-speaking hospitalised adults from general medical service in urban, academic safety-net medical centre who participated in the Project Re-Engineered clinical trial (clinicaltrials.gov identifier: NCT00252057 ). Main outcome measure: The primary end point was hospital utilisation, defined as total emergency department visits and hospital readmissions within 30 days after index discharge. Results: Female subjects had a rate of 29 events for every 100 people and male subjects had a rate of 47 events for every 100 people (incident rate ratio (IRR) 1.62, 95% CI 1.28 to 2.06). Among men, risk factors included hospital utilisation in the 6 months prior to the index hospitalisation (IRR 3.55, 95% CI 2.38 to 5.29), being unmarried (IRR 1.72, 95% CI 1.12 to 2.64), having a positive depression screen (IRR 1.53, 95% CI 1.09 to 2.13) and no primary care physician (PCP) visit within 30 days (IRR 1.64, 95% CI 1.08 to 2.50). Among women, the only risk factor was hospital utilisation in the 6 months prior to the index hospitalisation (IRR 3.08, 95% CI 1.86 to 5.10). Conclusions: In our data, male subjects had a higher rate of hospital utilisation within 30 days of discharge than female subjects. For men—but not for women—risk factors were being retired, unmarried, having depressive symptoms and having no PCP visit within 30 days. Interventions addressing these factors might lower hospital utilisation rates observed among men.